Spread of the mcr-1 colistin-resistance gene in Escherichia coli through plasmid transmission and chromosomal transposition in French goats - Treilles, Michaël; Châtre, Pierre; Drapeau, Antoine; Madec, Jean-Yves; Haenni, Marisa (Frontiers in Microbiology, 2023)
Introduction Colistin-resistance widely disseminated in food-producing animals due to decades of colistin use to treat diarrhea. The plasmid-borne mcr-1 gene has been extensively reported from bovine, swine and chicken worldwide, but smaller productions such as the goat farming sector were much less surveyed. Methods We looked for colistin-resistant isolates presenting plasmid-borne genes of the mcr family in both breeding (n=80) and fattening farms (n=5). Localization of the mcr-1 gene was performed using Southern blot analysis coupled to short-read and long-read sequencing. Results Only the mcr-1 gene was identified in 10% (8/80) of the breeding farms and four over the five fattening farms. In total, 4.2% (65/1561) of the animals tested in breeding farms and 60.0% (84/140) of those tested in fattening farms presented a mcr-1-positive E. coli. The mcr-1 gene was located either on the chromosome (32.2%) or on IncX4 (38.9%) and IncHI2 (26.8%) plasmids. As expected, both clonal expansion and plasmidic transfers were observed in farms where the mcr-1 gene was carried by plasmids. Tn6330 transposition was observed in the chromosome of diverse E. coli sequence types within the same farm. Discussion Our results show that the mcr-1 gene is circulating in goat production and is located either on plasmids or on the chromosome. Evidence of Tn6330 transposition highlighted the fact that chromosomal insertion does not impair the transmission capability of the mcr-1 gene. Only strict hygiene and biosecurity procedures in breeding farms, as well as a prudent use of antibiotics in fattening farms, can avoid such complex contamination pathways.